Os sistemas pedológicos e a paisagem na bacia da Sanga Clara Marechal Cândido Rondon-PR - Magalhães, Vanderlei Leopold (2008)
The municipality of Marechal Cândido Rondon, as well as the whole west region of Paraná state, based its economy, specially, into the agricultural sector. In this sense, researchs have to be the ones that value the environment so that the ecological potential and environment vulnerability should be evaluated. So, the subject area of this project gather informations about the geoecological and social economics structure of Margarida district, particularly Clara river first order basin that belongs to Marechal Cândido Rondon municipality. These informations were obtained by field labor, which included morphological and pedological studies, photographs, and interviews with the basin land owners. The development of the cartographic documents (hipsometria map, soils map and soil management map), ruled by the theoretical and methodological procedures of pedological cover structural analysis and systemic analysis, allowed to identified the higher and lower levels of vulnerability of the geoecological structure of Clara river basin and its surroundings, represented in the environment vulnerability map